WILL FOOD SECURITY BE AFFECTED BY RICE PRICE RISE - Akbarovich, Yadgarov Akram (PT ANTIS International Publisher, 2024)
The article analyzes the importance of ensuring food security today and the reasons for the increase in the price of rice in the world based on international statistical data